Tensile behavior of UHPC wet joints for precast bridge deck panels. (1st May 2023) - Jia, Junfeng; Ren, Zhangdi; Bai, Yulei; Li, Jian; Li, Bin; Sun, Yagang; Zhang, Zhixin; Zhang, Jianxun
Highlights: Five full-scale BDPs were designed to investigate the tensile behavior of wet joints. The initial cracks occurred at the joint interface of the PBDPs. The non-contact and contact lap U-bars have similar mechanical properties. The 200-mm-width UHPC wet joint has a higher tensile bearing capacity. Based on the strut-and-tie model and failure mode, a modified calculation formula was proposed. Abstract: Precast bridge deck panels (PBDPs) have been widely used in bridge engineering in the past decade. However, as the crucial part of connecting adjacent precast members, wet joints are often regarded as the weakest link in the bridge superstructure. To narrow the width of wet joints and reduce the assembling accuracy of U-bars, a total of five full-scale bridge deck panels (BDPs) were designed, which included four precast bridge deck panels with wet joints and one monolithic cast-in-place bridge deck panel (MCIPBDP). The major design variables included reinforcement types (straight bar and U-bar), U-bar lap details (non-contact lap and contact lap) and wet joint filling materials (NC and UHPC). The axial tensile loading tests were conducted to evaluate the tensile behavior of five BDPs. The experimental results demonstrated that all specimens experienced ductile failure, and finally failed due to the yielding of reinforcements. However, due to the insufficient lap length of 150 mm for the specimen P-NS-U200, bond slip appeared, and its ultimate tensile capacity decreased by 23.2% compared to the specimen P-NU-U200. Regarding the specimens P-NU-U200 and P-CU-U200, the difference in ultimate strength between non-contact lap and contact lap was within 3%. In addition, compared with the 500-mm-width normal concrete (NC) wet joint, the tensile capacity of the 200-mm-width UHPC wet joint was increased by 8.8%. Finally, based on the strut-and-tie model and failure mode, a modified calculation formula was proposed for estimating the tensile capacity of PBDPs. The predicted tensile capacity agrees well with the experimental results. The research provides a reference for engineers to guide the project's construction and apply UHPC wet joints in practical engineering.